Ноопедагогіка культури здоров’я в контексті підготовки вчителя початкових класів - Давидюк, Галина; Кардашук, Наталія; Поліщук, Наталія (Східноєвропейський національний університет імені Лесі Українки, 2018)
У статті висвітлюються основні напрямки підготовки вчителів початкових класів до формування культури здоров‟я молодших школярів на основі ноопедпгогіки. Головна увага приділяється індивідуальному підходу до особистості, врахуванні її природних задатків та їх тривалому цілеспрямованому розвитку. Завдання викладача культури здоров‟я полягає в теоретичній і практичній підготовці молодших спеціалістів на вирішення завданнь гармонійного розвитку духовних, психічних і фізичних сил учнів, їхньої оптимальної біосоціальної адаптації до середовища проживання. The article covers the main directions of preparation of primary school teachers for the formation of a culture of health of junior pupils based onnoopedagogy. The main attention paid to the individual approach to personality, taking into account its natural instincts and their long-term purposeful development. The task of the teacher of health culture consists of theoretical and practical training of junior specialists for the tasks of harmonious development of spiritual, psychic and physical forces of students, their optimal biosocial adaptation to the environment. The authors are convinced that modern education requires innovations in the field of science and education, the elimination of all unnecessary accumulation in educational disciplines, as well as a deeper penetration into the phenomenon of modern scientific achievements. The teaching of all disciplines should be rethought and rebuilt under the foundations of a culture of health. Pedagogy should be transformed into noopedagogy (spiritual education). In the first place, the training must eradicate the rudeness that destroys the thin matter of the child. The upbringing of spirituality opens up the prospects for every child in the world, if the one chooses his own path of development through creativity. The culture of health on the principles of noopedagogy forms the desire of children to work continuously on themselves. After any work (physical or mental), people always become kinder and more patient. Therefore, the teacher must teach children to work and praise for a positive result. These postulates the teacher of culture of health at the pedagogical college should lay in the consciousness of future specialists.
Keywords: культура здоров’я; ноопедагогіка